2011
DOI: 10.1039/c0cp02777d
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic and electronic structure of vanadyl pyrophosphate from density functional theory

Abstract: We have studied the magnetic structure of the high symmetry vanadyl pyrophosphate ((VO) 2 P 2 O 7 , VOPO), focusing on the spin exchange couplings, using density functional theory (B3LYP) with the full three-dimensional periodicity. VOPO involves four distinct spin couplings: two larger couplings exist along the chain direction (a-axis), which we predict to be antiferromagnetic, J OPO = À156.8 K and J O = À68.6 K, and two weaker couplings appear along the c (between two layers) and b directions (between two ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…7 We found that the band structures, projected density of states, and Mulliken charge distribution are very similar for the two forms, and hence we expect the surface chemistry to be similar. 8 Additionally since all the chemistry is initiated by the O(1)=P active site, we calculated the binding energy (D H ) of a free hydrogen atom to O(1)=P using the low symmetry, ambient pressure form of oxidized VOPO (X 1 -VOPO 4 ) and compared the result to that using the high symmetry, high pressure form of oxidized VOPO. We found the two D H 's are quite similar (86.1 kcal/mol vs. 84.3 kcal/mol).…”
mentioning
confidence: 99%
“…7 We found that the band structures, projected density of states, and Mulliken charge distribution are very similar for the two forms, and hence we expect the surface chemistry to be similar. 8 Additionally since all the chemistry is initiated by the O(1)=P active site, we calculated the binding energy (D H ) of a free hydrogen atom to O(1)=P using the low symmetry, ambient pressure form of oxidized VOPO (X 1 -VOPO 4 ) and compared the result to that using the high symmetry, high pressure form of oxidized VOPO. We found the two D H 's are quite similar (86.1 kcal/mol vs. 84.3 kcal/mol).…”
mentioning
confidence: 99%
“…The nature of chemical bonds in VOPO was explored by investigating the variations in V-O bond lengths as a functional of strain along the a axis through compressing and stretching the cell parameter a by 3 and 5%, respectively. [1] Figure 2. Polyhedral views of the crystal structure of the high-symmetry form of VOPO.…”
Section: Electronic Structures Of (Vo)2p2o7mentioning
confidence: 99%
“…Based on these asymmetric variations of the V-O bond lengths, we concluded that V-O(2) is a rigid covalent single bond while V-O(3) is a fragile dative bond (Scheme 1(b)). [1] This valence bond description plays an important role in understanding the catalysis. …”
Section: S2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few vanadyl chain compounds of vanadium-phosphate type which are relevant to catalytic applications. [26][27][28][29][30] Examples of carboxylatebridged vanadyl chains are scarce, and they include formate, 31 acetate, 32,33 glycolate 32,33 and benzoate 34 as bridges. Theoretical calculations have suggested that the band gap in such systems may be tuned from semiconducting to metallic states, broadening the application possibilities of hybrid inorganicorganic compounds.…”
Section: Introductionmentioning
confidence: 99%